Determination of parameters for wet grinding of phosphates in a laboratory ball mill and classification in a hydrocyclone - Lazić, Predrag; Nikšić, Đurica; Živković, Vladan; Todorović, Nemanja (Podzemni radovi, 2024)
The company Elixir Prahovo uses dry grinding of raw phosphate in its production process. However, due to increased moisture in the raw phosphate causing difficulties in the dry grinding phase, the possibility of introducing wet grinding is being considered at the industrial plant in Prahovo. The moisture content of the incoming raw phosphate varies from barge to barge, ranging between 5-10% H2O, which is very high for the dry grinding process and create certain problems in the transportation system (the system of apron conveyors). To assess the possibility of wet grinding of phosphates, predefined laboratory tests were conducted at the Department of Mineral Processing of the Faculty of Mining and Geology in Belgrade. This paper presents a portion of the results obtained during the aforementioned tests, which relate to the tested sample and its processing, as well as the determination of the particle size distribution of the initial sample, density, and bulk mass of phosphate ore. T In further investigations, grindability tests were conducted in a laboratory ball mill, and hydrocyclone tests were conducted on the ground phosphate in a laboratory hydrocyclone. Based on the results of these investigations, the necessary technological parameters have been determined to propose a scheme for the technological process of wet grinding and classification of phosphate. These parameters primarily relate to the material distribution in the hydrocyclone, pulp density in classification, and the particle size distribution of the ground phosphate.